2019
DOI: 10.1186/s12931-019-1010-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and minimal important differences of SF-36 in Idiopathic Pulmonary Fibrosis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a rare disease with a median survival of 3–5 years after diagnosis with limited treatment options. The aim of this study is to assess the psychometric characteristics of the Short Form 36 Health Status Questionnaire (SF-36) in IPF and to provide disease specific minimally important differences (MID). Methods Data source was the European IPF Registry (eurIPFreg). The psychometric properties of the SF-36 version 2 were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
(50 reference statements)
2
38
0
1
Order By: Relevance
“…The aim of SF-36 is to characterize and understand the relationship between the selected baseline clinical covariates, the physical component score (PCS), and the mental component score (MCS) [25]. This questionnaire is a validated instrument for assessing HRQoL and has been applied to a variety of chronic medical conditions, including IPF [7]. The SF-36, as described in the name, is a 36-item patient-reported questionnaire that evaluates eight health domains: physical functioning (10 items), bodily pain (2 items), role limitations due to physical health problems (4 items), role limitations due to personal or emotional problems (4 items), emotional well-being (5 items), social functioning (2 items), energy/fatigue (4 items), and general health perceptions (5 items).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of SF-36 is to characterize and understand the relationship between the selected baseline clinical covariates, the physical component score (PCS), and the mental component score (MCS) [25]. This questionnaire is a validated instrument for assessing HRQoL and has been applied to a variety of chronic medical conditions, including IPF [7]. The SF-36, as described in the name, is a 36-item patient-reported questionnaire that evaluates eight health domains: physical functioning (10 items), bodily pain (2 items), role limitations due to physical health problems (4 items), role limitations due to personal or emotional problems (4 items), emotional well-being (5 items), social functioning (2 items), energy/fatigue (4 items), and general health perceptions (5 items).…”
Section: Data Collectionmentioning
confidence: 99%
“…ILDs may occur due to a known cause such as drugs, connective tissue disease (CTD), hypersensitivity to inhaled organic antigens (hypersensitivity pneumonitis, HP), or sarcoidosis; whilst others, especially sporadic idiopathic interstitial pneumonias (IIPs), have no identifiable origin [4]. Of them, idiopathic pulmonary fibrosis (IPF) is associated with the highest burden and poor prognosis [5][6][7]. Apart from IPF, other IIPs include idiopathic non-specific interstitial pneumonia (NSIP), respiratory bronchiolitis-ILD (RB-ILD), desquamative interstitial pneumonia (DIP), cryptogenic organizing pneumonia (COP), acute interstitial pneumonia (AIP), and some other rare forms [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the IPF-PRO registry, the observed within-patient correlations for QOL metrics (Objective 2) showed that physical QOL domains were most strongly correlated with overall scores (eg, total SGRQ and SF-12 PCS), suggesting that QOL in IPF may be strongly affected by physical limitations, as has been reported. 29 Given the lack of consensus-based standards for characterization of disease severity in IPF, our study adds to the literature by describing within-patient concordance between severity classifications. We observed modest correlations between GAP and CPI (R w 0.60), indicating that each metric may offer independent information, an interesting finding given that similar clinical variables are used in their calculations.…”
Section: Discussionmentioning
confidence: 97%
“…9 Generic PROMs such as Euroqol-5D and short form-36 have been used in this condition. 32,33 Disease-specific PROMs, such as Saint George Respiratory Questionnaire (SGRQ) 34 and COPD assessment Test (CAT), 35 although not specific for idiopathic pulmonary fibrosis, have also been used. In addition, idiopathic pulmonary fibrosis-specific tools such as SGRQ-IPF, 36 the cross Atlantic tool to assess quality of life in IPF (ATAQ-IPFca) 3,7 and King's Brief Interstitial Lung Disease (K-BILD)…”
Section: Proms and Prems For Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Such information needs to be delivered at the first visit and revisited throughout the course of the disease. 33 and symptoms (MYMOP) 57 Health care experience disconnected from patient reality and daily needs 54,79 Lack of: 1) MDT and PC approach; 2) prioritization of symptom/need assessment; 3) integrated advanced care planning; 4) communication and information skills…”
Section: Early and Accurate Diagnosis With Patient-centered Educationmentioning
confidence: 99%